ANALISIS INDEKS AIKEN UNTUK MENGETAHUI VALIDITAS ISI INSTRUMEN ASESMEN KETERAMPILAN SOSIAL - Yussi Martha Sukma Astuti (Jurnal Kualita Pendidikan, 2023)
This study aims to analyze the content validity of the social skills assessment instrument based on the Aiken validity index, with the aim that the instrument can be used in accordance with the indicators. The research method used is a quantitative descriptive research method based on the results of content validity which is calculated using the Aiken formula. Content validity data were obtained from 8 experts, namely 8 grade VI elementary school teachers through Focus Group Discussion (FGD). The content validity test in this study used four criteria in the assessment, namely Not Relevant (TR), Less Relevant (KR), Quite Relevant (CR), and Relevant (R). The social skills assessment instrument produced 18 valid items with an Aiken index ? 0.75 and 2 invalid items with an Aiken index < 0.75. Keywords: Content Validity, Aiken, Social Skills Assessment